A utilização do google site e kahoot como instrumentos didáticos para o ensino e aprendizagem de cálculos estequiométricos - Comper, Angélica Vermelho (2024)
Chemistry teachers have a responsibility to educate citizens and develop in them the knowledge of applicability in their lives. It becomes challenging when one realises that content is taught in a traditional way, using only a whiteboard and a marker, often in a memoristic manner. This approach does not stimulate students' cognitive development or take into account their learning experiences. By seeking to demystify this traditionalism, the incorporation of digital technologies into chemistry teaching has the potential to enrich the teaching and learning process for students. This can result in greater interest, motivation and connection on the part of students, who can demonstrate more engagement when learning through active methodologies. Thus, the aim of this dissertation is to analyse and detail how the use of a Google Site and the Kahoot game, in the context of Stoichiometric Calculations, can benefit the teaching and learning process of stoichiometry concepts for the students of two secondary school classes in the public state school system in the municipality of Colatina, state of Espírito Santo. As for the procedures, the research followed a qualitative design from a descriptive perspective, using questionnaires as data collection tools at various points in the research and divided into two parts. The first part corresponds to the presentation of the stoichiometry content through the Google Site platform. The second phase of this study consists of implementing a digital game to assess student learning. The results of the research show that students have greater difficulty in interpreting text to solve stoichiometric calculations and the use of technology has provided substantial benefits for teaching and learning. This is evident in all the activities carried out in the classroom. This research tends to provide the academic community with ways of highlighting students' difficulties and doubts in relation to the teaching of stoichiometry.